Impact of cannabidiol on reward- and stress-related neurocognitive processes among individuals with opioid use disorder: A pilot, double-blind, placebo-controlled, randomized cross-over trial - Suzuki, Joji; Prostko, Sara; Szpak, Veronica; Chai, Peter R.; Spagnolo, Primavera A.; Tenenbaum, Ruth E.; Ahmed, Saeed; Weiss, Roger D. (Frontiers in Psychiatry, 2023)
Introduction: Opioid use disorder (OUD) continues to be a significant public health concern. Medications for OUD (MOUD) such as buprenorphine reduce overdose mortality, but relapses occur often, leading to adverse outcomes. Preliminary data suggest that cannabidiol (CBD) may be a potential adjunctive treatment to MOUD by attenuating cue-reactivity. This pilot study sought to evaluate the impact of a single dose of CBD on reward- and stress-related neurocognitive processes implicated in relapse among those with OUD. Methods: The study was a pilot, double-blind, placebo-controlled, randomized cross-over trial aimed at assessing the effects of a single dose of CBD (Epidiolex®) 600mg or matching placebo administered to participants with OUD receiving either buprenorphine or methadone. Vital signs, mood states, pain, opioid withdrawal, cue-induced craving, attentional bias, decision making, delayed discount, distress tolerance, and stress-reactivity were examined at each testing session on two separate testing days at least one week apart. Results: Ten participants completed all study procedures. Receipt of CBD was associated with a significant decrease in cue-induced craving (0.2 vs 1.3, p=0.040), as well as reduced attentional bias toward drug-related cues as measured by the visual probe task (-80.4 vs 100.3, p=0.041). No differences were found among all the other outcomes examined. Discussion: CBD may have promise as an adjunct to MOUD treatment by attenuating the brain response to drug-related cues, which in turn may reduce the risk of relapse and overdoses. Further research is warranted to evaluate the potential for CBD as an adjunctive therapy for individuals in treatment for OUD.